PSVIII-29 Galectin 9 secretion in cow milk a marker for homostasis and health. (7th December 2018) - Mulakala, B; Eluka-Okoludoh, E; Adjei-Fremah, S; Asiamah, E; Ekwemalor, K; Ismail, H; Ibrahim, S; Worku, M
Abstract: Infectious and metabolic diseases are the significant hindrance to animal production. Galectins (Gal) are β-galactosidase binding proteins that can modulate inflammation following external and internal secretion from the cell. Galectin 9 is a tandem repeat member of Gal involved in cell activation, pathogen destruction and immunosuppression. Binding of Gal 9 to its receptor T cell immunoglobulin and mucin domain 3 (TIM-3) on immune cells can modulate the inflammatory response. Migration of neutrophils from blood contributes to increased Somatic cell count (SCC) in Mastitis. The possible role of TIM -3 and its ligand Gal 9 in animal health and disease needs to be defined. The objective of this study was to determine the transcription of TIM-3, Gal 9 and secretion of Gal 9 in cow milk. Milk was collected from the udder of 10 clinically healthy Holstein cows. Dairy herd index reports were used to assign 5 cows to high or low SCC groups. Total RNA was isolated from milk somatic cells, pooled and converted to cDNA, for Real-time PCR. Specific primers for cow TIM-3 and LGALS 9 were designed using the NCBI Primer 3 tool. Housekeeping gene β-actin served as an internal control. Whey was extracted from whole milk. Cow Gal 9 specific ELISA kits were used for assessing secretion. Data were analyzed using Proc ANOVA procedure in SAS 9.4. Transcription of TIM-3 was not detected in milk. However, Gal 9 was transcribed and secreted. The level of secretion was 33% higher in LSCC. The observed increase may be important in homeostasis and health thus warrants further study with more cows. Future studies should look at cell surface expression of TIM-3 using more animals.